Investigation of the Protective Effect of Nerolidol on Dehydroepiandrosterone-induced Polycystic Ovary Syndrome in Female Rats - Yuce, Hande; Turkmen, Nese Basak; Aydin, Muhterem; Taslidere, Asli; Dogan, Aysegul; Ozek, Dilan Askin; Unuvar, Songul (Wiley, 2023)
[Abstract Not Available]
Keywords: Nerolidol; Polycystic Ovary Syndrome; Oxidative Stress; Apoptosis; Dehydroepiandrosterone.